Knowledge and clinical behavior on antiresorptive medications and osteonecrosis of the jaws: a cross-sectional study - Daniel Amaral Alves MARLIÉRE; Tony Eduardo COSTA; Rafael Binato JUNQUEIRA; Saulo de Matos BARBOSA; Luciana ASPRINO; Henrique Duque de Miranda CHAVES NETTO (Faculdade São Leopoldo Mandic, 2019)
Objective: This present study assessed the knowledge and clinical behaviors of dentists on antiresorptive medications (AM) and osteonecrosis of the jaws (ONJ). Methods: A cross-sectional study was performed by a questionnaire applied to a sample of 101 dentists. It inquired about general information, knowledge on AM and ONJ, behaviors regarding clinical cases of patients, and knowledge acquisition sources. Kappa coefficient (ƙ) checked the questionnaire's reliability. Descriptive statistics were computed, Fisher's test assessed the association between behaviors and knowledge. Logistic regression analysis to estimate propensity score. Statistical significance was set at p ≤ 0.05. Results: The reliability showed good agreement (ƙ = 0.8). 59% of the dentists reporting to know AM, 83% believing it is important to know whether patients took AM during anamnesis and 53% indicating that they knew that ONJ was a side effect of AM. However, 5% of the dentists informed that they could fully recognize brand name of AM, and that 50% would not perform any dental invasive treatment, with 73% acquiring knowledge on AM and ONJ from scientific articles. Conclusion: dentists recognized AM, but they would not be comfortable treating patients who had taken AM or developed ONJ. Educational efforts might be made to promote the knowledge of dentists.